Potential Use of Malaysian Thermal Power Plants Coal Bottom Ash in Construction - Abubakar, Abdulhameed Umar; Baharudin, Khairul Salleh (International Journal of Sustainable Construction Engineering and Technology, 2012)
As Malaysia focuses its attention to the call for a “greener” culture, so did the engineers and those in the scientific community especially the construction industry who is a major contributor to the depletion of green house gases. The engineering and construction community has now taken up the challenge for the use of “green and recycled by-products” in construction. One of those by-products is the Coal Bottom Ash (CBA) from thermal power plants that faces an increasing production running into hundreds of thousand tonnes in Malaysia alone, and its method of disposal is relegated to landfills alone with no other commercial usage. The construction industry is now forced to rethink on the utilization of the industrial by-products as supplementary materials due to the continuous depletion of natural aggregates in construction. A significant amount of research has been conducted elsewhere on CBA to ascertain its pozzolanic activity, compressive strength in concrete and mortar, durability, water absorption characteristics and density, in order to ensure its usage as a construction material. In this paper, a critical review of the strength characteristics of concrete and mortar as influenced by CBA as partial replacement of fine aggregate is presented based on the available information in the published literatures. Diverse physical and chemical properties of CBA from different power plants in Malaysia are also presented. The influence of different types, amounts and sources of CBA on the strength and bulk density of concrete is discussed. The setting time, workability and consistency as well as the advantages and disadvantages of using CBA in construction materials are also highlighted. An effective utilization of CBA in construction materials will significantly reduce the accumulation of the by-products in landfills and thus reduce environmental pollution.